Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T19:40:03+01:00
Zad 2 / 93

a ) 2x - y = 5
- y = 5 - 2x / * ( - 1 )
y = - 5 + 2 x
y = 2x - 5

b ) 1/3 y = x - 3 / : 1/3
y = x - 3 * 3
y = 3 x - 9

e ) 4 x + 2 y = 1
2 y = 1 - 4 x / : 2
y = 1/2 - 2 x

d ) 2/3 x = 3/4 y
3/4 = 2/3 x / : 3/4
y = 8/9 x

f ) 6x-2/3y = 2
- 2/3 = 2 - 6x / : ( - 2/3 )
y = ( 2-6x) : ( - 2/3 )
y = ( 2-6x ) * ( - 3/2 )
y = - 3 + 9 x

c ) 3(x-y) = 2x
3x - 3y = 2x
- 3y = 2x = 3x
- 3y = -x / : ( - 3 )
y = 1/3 x

uff ; ) juz , cale zadanko 2 ; )) .

zad 4 : )

a ) 3x = 12
x-y=1


x=12 / : 3
x - y = 1


x = 4
4- y = 1


x = 4
- y = 1 - 4 / * 1


x = 4
y = - 1 + 4


x = 4
y = 3

prosze : ) daje tylko tyle bo nie mam czasu . ale mam ndzieje ze sie przyda ; )
3 3 3